Glycolysis in the tumor microenvironment shapes dendritic cell function and antitumor immunity - Zhang, Bo; Zhao, Linlin; Li, Huzi; Wang, Na; Wang, Xuerui; Shang, Lihan; Sun, Bingsheng; Kong, Fanming (Frontiers in Immunology, 2026)
Dendritic cells (DCs) are central orchestrators of antitumor immunity, but their functions are markedly curtailed by glycolysis-dominated metabolic constraints in the tumor microenvironment (TME). This review focuses on two interconnected dimensions: tumor-derived metabolic stressors that suppress DC activation and the intrinsic metabolic programs of DC subsets that define their immunogenic potential. Lactate accumulation, hypoxia, adenosine signaling, and lipid overload disrupt antigen cross-presentation, type I interferon (IFN-I) production, and DC migration, collectively biasing DCs toward tolerogenic or checkpoint-high states. At the same time, subset-specific metabolic wiring—such as reliance on oxidative phosphorylation (OXPHOS) and fatty acid oxidation (FAO) in conventional type 1 DCs (cDC1s), glycolysis-dependent Th17-skewing capacity in conventional type 2 DCs (cDC2s), and pronounced hypoxia sensitivity in plasmacytoid DCs—creates distinct vulnerabilities that can be therapeutically exploited. We further summarize emerging strategies to restore DC metabolic fitness, including blockade of tumor glycolysis, intrinsic DC metabolic rewiring, modulation of immunometabolites and redox balance, use of natural products and nanomaterials, and rational combinations with radiotherapy or immune checkpoint blockade. Finally, we outline translational priorities such as single-cell and spatial mapping of DC metabolic heterogeneity, development of metabolism-linked biomarkers, and integration of DC-targeted interventions into existing immunotherapy frameworks. Together, these insights position DC metabolism as a critical lever to reprogram the TME and to enable more durable antitumor immunity.